Robots and Unions: The Moderating Effect of Organised Labour on Technological Unemployment - Henri Haapanala; Ive Marx; Zachary Parolin (Institute of Labor Economics (IZA), 2022)
We analyse the moderating effect of trade unions on industrial employment and unemployment in countries facing exposure to industrial robots. Applying random effects within-between regression to a pseudo-panel of observations from 28 advanced democracies over 1998-2019, we find that stronger trade unions in a country are associated with a greater decline in the industry sector employment of young and low-educated workers. We also show that the unemployment rates for low-educated workers remain constant in strongly unionised countries with increasing exposure to robots, whereas in weakly unionised countries, low-educated unemployment declines with robot exposure but from a higher starting point. Our results point to unions exacerbating the insider-outsider effects of technological change within the industrial sector, which however is not fully passed on to unemployment.
Keywords: J5; 330; trade unions; technological change; outsiders/insiders; dual labour market; unemployment; labour economics